SCHOLARS’ PRAISES OF IMAM AL-TIRMIDHI - Temirov Ibrohimjon Qobiljonovich (International Journal of Literature and Language Studies, 2026)
Annotation: This article examines the life, scholarly activities, and contribution to the science of Hadith of Imam Abu Isa Muhammad ibn Isa al-Tirmidhi, one of the greatest muhaddiths and prominent representatives of Hadith scholarship. It also presents the views of renowned scholars such as Imam al-Bukhari, Imam al-Hakim, al-Dhahabi, Ibn Hibban, and others regarding Imam al-Tirmidhi, highlighting his distinguished status in knowledge, memorization of Hadith, piety, and asceticism. The article analyzes Imam al-Tirmidhi’s contribution to the development of Hadith studies, particularly his services in the classification and evaluation of Hadiths.